HUBUNGAN ANTARA PENGUNGKAPAN ASPEK SOSIAL EKONOMITERHADAP SIZE, LIKUIDITAS, SOLVABILITAS DAN STRUKTUR KEPEMILIKAN (STUDIKASUS: JII DAN NON JII) - Uun Sunarsih (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2009)
Today, companies start to have concerning on social activities. Accounting as a business tool is required to respond business development. Accounting's role emerges with social accounting to communicate companies social activities in order to get legitimation and to fulfil social accountability from both direct and indirect stakeholders. This research is aimed to know the disclosure of socio economic aspect of companies listed both at JII and Non JII and its relation with size, liquidity, solvability and ownership structure. Research sample consisted of the following industries listed in 2004: agricultural, mining and mining service, food and beverage, automotive, consumer goods, communication, transportation service, plastic and glass product, pharmaceuticals, real estate and property, lumber and wood product, electronic and office equipment and cement. Data analysis used in this study is two different mean and logistic analysis. The researchfinds that the average of social aspect disclosure for companies listed at JII are larger than companies listed at Non JII. This can be seen that the average of socio economic aspect disclosure at JII reached 38,53% and the most disclosed are consumer and product issue as of 63,33% followed by labor issue 57,43%, community issue 19,67% and environment and energy issue 13,67%. While for companies listed at Non JII, the average of socio economic disclosure aspect reached 34,11% andd the most disclosed are labor issue as of 59,95% followed by consumer and product issue 45,98%, community issue 18,56% and environment and energy issue 11,95%. The relation between size, liquidity, solvability and ownership structure for companies listed at JII after having variable reduction test, the result shows that only ln_size and ownership structure which are significant ata = 5%, whereas for the companies listed at Non JII only ownership structure which is significant at a = 5%.Keywords: Social Accounting, company size, liquidity, solvability and ownership structure.